2015
DOI: 10.5750/ejpch.v3i4.1021
|View full text |Cite
|
Sign up to set email alerts
|

Renewing the expertise of health and social care professionals to provide integrated care: Evaluation of an intervention in a deprived Dutch neighbourhood

Abstract: Rationale, aims and objectives: Multimorbidity in deprived populations is associated with longer hospital stays, more avoidable admissions and complications, higher costs, and lower satisfaction with available services. While integrated care has been proposed as a solution, the expertise of professionals to deliver this type of care has received little attention. Our case study evaluates an intensive intervention in a deprived neighbourhood in the Netherlands, launched in 2008, to tackle multimorbidity and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The study period ranges from 2006 to 2011, the period in which the pilot interventions were implemented (Additional file 1 : Table S1). A previous study has shown that during the intervention period, primary care professionals in the intervention district increasingly accustomed to a more integrated working approach over this period of time [ 25 ]. We therefore expect the impact of the integrated care approach on health care use to become increasingly stronger over the course of time.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study period ranges from 2006 to 2011, the period in which the pilot interventions were implemented (Additional file 1 : Table S1). A previous study has shown that during the intervention period, primary care professionals in the intervention district increasingly accustomed to a more integrated working approach over this period of time [ 25 ]. We therefore expect the impact of the integrated care approach on health care use to become increasingly stronger over the course of time.…”
Section: Methodsmentioning
confidence: 99%
“…An intervention was implemented with the aim to stimulate primary care professionals to improve their expertise, attitude, behaviour and tools to better support them to provide more comprehensive forms of integrated care. Within this area-based programme improvement of integrated care approaches led to professionals taking on a population health orientation, a focus on prevention, applying a generalist view to patients enabling the undertaking of cross domain actions, and coaching behaviour to empower patients to become participants in their own care processes and self-manage their own health [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations